Share parenting after the divorce - Kamaruddin, Zaleha (Star Publications (M) Bhd., 2011)
Until the courts, both civil and syariah, stop ordering ‘visitation’ and start giving fathers the same recognition given to mothers, children in divorces will continue to suffer.